2019
DOI: 10.4236/jep.2019.102014
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Assessment of Wastewater Systems: An Environmental and Economic Approach

Abstract: To address current challenges regarding sustainable development of wastewater treatment and provide scientific support in decision procedures towards sustainable solutions, new approaches, frameworks and methodologies about different possible solutions and their potential sustainability implications are needed. One way to facilitate sustainability assessment of wastewater is Life Cycle Assessment (LCA) methodology; however, it fails to map the full scope of wastewater impacts. This paper presents a framework t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Database of the National Institute of Geography and Statistics (INEGI) portal. Three options for coefficients of variation (CV) are High, CV ranging from (0-15); Medium, CV in (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and Low, CV in 30% and more. Data accuracy by indicator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Database of the National Institute of Geography and Statistics (INEGI) portal. Three options for coefficients of variation (CV) are High, CV ranging from (0-15); Medium, CV in (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and Low, CV in 30% and more. Data accuracy by indicator.…”
Section: Methodsmentioning
confidence: 99%
“…[21] Later, it was extended to environmental and economic analysis. [22] Finally, Amaral et al conducted a sustainability assessment of biogas treatment plants in Brazil using the S-LCA for the social dimension. [23] On the other hand, Opher et al conducted a comparative sustainability assessment of the reuse of domestic wastewater recovered from toilet flushing and landscape irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that water systems need an S-LCA methodology with specific indicators to help the decision-making process. Padilla-Rivera et al (2019) proposed a useful metric to decide which is the best WWT from an environmental, social and economic perspective. In selecting the appropriate indicators, they considered that, up to now, the emphasis on wastewater has been on the epidemiological features and their consequences on health and on the social aspects of its use, mainly linked to irrigation.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Changes in natural systems caused by nature-intensive sectors of the economy, including energy, are manifested in the form of significant material and energy flows (Davankov et al, 2017). The movement of ecosystem components and the extraction of natural resources lead to the degradation of the natural environment and put it in an unbalanced state (Padilla-Rivera et al, 2019). The sustainability assessment of energy biosphere flows and energy of regional economic activity should be based on the use of a general criterion of material input (Giljum, 2011).…”
Section: Identification Of Patterns Between the Level Of Development Of Traditional And Renewablementioning
confidence: 99%